2014
DOI: 10.1515/pr-2014-0009
|View full text |Cite
|
Sign up to set email alerts
|

The role of prosody and gesture in the perception of mock impoliteness

Abstract: Within the impoliteness literature, an important distinction has been made between genuine and mock (or non-genuine) impoliteness (Culpeper 1996(Culpeper , 2011 Bernal 2008, among others). Even though mock impoliteness has generally been analyzed within an impoliteness framework, recent proposals suggest that it is an essentially different pragmatic phenomenon that requires a continuous conversational evaluation (Haugh and Bousfield 2012). The present study had the goal of assessing the offline evaluation proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…Similarly, Nadeu and Prieto (2011) found that Catalan speakers perceptually associated a high pitch range with politeness, but that this also depended on whether the speaker was smiling or had a neutral facial expression. In another study on Catalan, McKinnon and Prieto (2014) found that prosody, as well as gesture, played an important role in differentiating between genuinely offensive politeness and jovial mock impoliteness. Participants in this study were much better at differentiating mock impoliteness from genuine impoliteness if they were provided with videos, rather than just audio recordings alone.…”
Section: Background On the Nonverbal Expression Of Politenessmentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, Nadeu and Prieto (2011) found that Catalan speakers perceptually associated a high pitch range with politeness, but that this also depended on whether the speaker was smiling or had a neutral facial expression. In another study on Catalan, McKinnon and Prieto (2014) found that prosody, as well as gesture, played an important role in differentiating between genuinely offensive politeness and jovial mock impoliteness. Participants in this study were much better at differentiating mock impoliteness from genuine impoliteness if they were provided with videos, rather than just audio recordings alone.…”
Section: Background On the Nonverbal Expression Of Politenessmentioning
confidence: 96%
“…Despite the obvious multimodal nature of most social phenomena, research on (im)politeness phenomena has traditionally focused mainly only on verbal means to express (im)politeness, such as polite words or honorific markers. Several authors have noted that the role of nonverbal communication is either downplayed or simply not addressed in past research (e. g., Winter and Grawunder 2012;Brown, Winter, Idemaru and Grawunder 2014;McKinnon and Prieto 2014). Culpeper (2011: 151) observes that "non-verbal cues such as gaze, facial expressions, body movements/gestures […] and the spatial positioning of the self play a key role in communication […] yet it is still an area that receives relatively little attention in communication and pragmatic studies."…”
Section: Introductionmentioning
confidence: 99%
“…McKinnon & Prieto investigate the role of prosody and gesture in the perception of mock and genuine impoliteness in Catalan [14]. They found that intonation contours, used in the different impoliteness condition did not occur in significantly different proportions, but there was a stronger tendency to use H+L* L% with genuine impoliteness.…”
Section: British English Television Quiz Show (The Weakest Link)mentioning
confidence: 99%
“…It has also been shown that it is not only the context sensu lato which contributes considerably to the reconstruction of the intended meaning, but also the production modalities of the utterance, e. g. gesture, facial expression and voice quality. It has been shown [13,6,14] that the speaker's overall communicative performance enables the addressee to interpret the utterance correctly. It is not only the special relationship between speaker and addressee, but their shared knowledge of the expected production formsgestures, facial expressions, prosody and context conditionswhich are necessary for 'oblique communication' to be understood as it is meant and not just in terms of what is said.…”
Section: Introductionmentioning
confidence: 99%
“…Yet politeness is not only encoded by lexical cues; facial gestures and prosody also play crucial roles in the perception of an utterance as polite or non-polite (see, e.g., [6,7]). One of the questions is therefore what role audiovisual prosody plays in guiding children to meaning.…”
Section: Introductionmentioning
confidence: 99%